The human Suv3 helicase interacts with replication protein A and flap endonuclease 1 in the nucleus - Venø, Susanne T. (Biochem J, 2011)
The hSuv3 (human Suv3) helicase has been shown to be a major player in mitochondrial RNA surveillance and decay, but its physiological role might go beyond this functional niche. hSuv3 has been found to interact with BLM (Bloom’s syndrome protein) and WRN (Werner’s syndrome protein), members of the RecQ helicase family involved in multiple DNA metabolic processes, and in protection and stabilization of the genome. In the present study, we have addressed the possible role of hSuv3 in genome maintenance by examining its potential association with key interaction partners of the RecQ helicases. By analysis of hSuv3 co-IP (co-immunoprecipitation) complexes, we identify two new interaction partners of hSuv3: the RPA (replication protein A) and FEN1 (flap endonuclease 1). Utilizing an in vitro biochemical assay we find that low amounts of RPA inhibit helicase activity of hSuv3 on a forked substrate. Another single-strand-binding protein, mtSSB (mitochondrial single-strand-binding protein), fails to affect hSuv3 activity, indicating that the functional interaction is specific for hSuv3 and RPA. Further in vitro studies demonstrate that the flap endonuclease activity of FEN1 is stimulated by hSuv3 independently of flap length. hSuv3 is generally thought to be a mitochondrial helicase, but the physical and functional interactions between hSuv3 and known RecQ helicase-associated proteins strengthen the hypothesis that hSuv3 may play a significant role in nuclear DNA metabolism as well.